(untitled) - Oka, H. I. (Tokyo, 1988)
Ecology and population biology of the common wild rice, genetic variations and envolutionary dynamics, the homeland of oryza sativa, Indica-japonica differentiation of rice cultivars, funtions and genetic bases of reproductive, variations in adaptability to environment, and germplasm conservation.
Keywords: Rice,Rice,Cây lúa; Origin